How startups can develop CSR to build brand reputation - Papa, Elena (My University, 2022)
This qualitative research study paper examines the integration of Corporate Social Responsibility (CSR) in building brand reputation and competitive advantage of SME startups. It seeks to explore the drivers, importance, and best practice applications of CSR activities by startups. It further analyzes customers' impressions of startup sustainability and CSR practices and the firm's reputation. The study adopted an interpretive study design (thematic analysis), focused on a sample of CSR specialists, advertisers, and startup owners, and revealed a reflection of the theoretical dimension of CSR in the study results. Specifically, the social size of CSR implementation and the adoption of practices that focus on human resources, the environment, and society at large, were captured in the data. Basic CRS principles, such as the need for the development and implementation of environmental awareness programs, volunteering, and labor, were commonly agreed by the participants as relevant emerging themes of the study. The results pointed out the importance of company ethics in shaping a healthy employee work environment and highlighted the critical role of the firm's purpose. The emphasis on building relationships with society as a whole and specifically with the community in which the company operates seems to be the key to the profitable implementation of CSR regarding brand reputation. The reciprocal relationship created between the customer who feels that the company is not solely for profit but in its connection with the community is the basis for a profitable course. Voluntary actions organized by the firm to support the community act as a means of building brand reputation.
Keywords: CSR; startups; branding; reputation management; ethics